Molecular analysis of the mitochondrial genome using a non-radioactive method on somaclonal variation in regenerated plants of primary CMS triticale plants - Weigel, Ralf; Wolf, Markus; Stierle, Micaela; Stoesser, Thomas; Hesemann, Claus-Ulrich (Triticale: today and tomorrow, 1996)
The mitochondrial DNA of primary hexaploid triticale with and without timopheevi cytoplasm and the corresponding wheat cross parents were characterized by hybridization experiments using six different mitochondrial gene probes and four different restriction enzymes for Southern blot analyses with the novel non-radioactive digoxigenin technique. Via somatic embryogenesis 623 triticale plants were regenerated. The mitochondrial genome of 159 plants was investigated. Somaclonal variation of the chondriome was found to a high percentage in regenerated plants with timopheevi, but only to a low percentage in individuals with maintainer cytoplasm. In sixteen cases rearrangements in the mitochondrial DNA were detected. Furthermore, obvious alterations in the stoichiometry of specific hybridization bands have occurred. Some of these stoichiometric differences depend on the triticale-type.
Gesehen am 22.02.2024